2021
DOI: 10.3390/ijerph18094892
|View full text |Cite
|
Sign up to set email alerts
|

Are the Physical Environments of Treatment Centres Meeting Recommendations for Patient-Centred Care? Perceptions of Haematological Cancer Patients

Abstract: The physical environment of a treatment centre may impact the well-being of patients and their perceptions of care. Outpatients with haematological cancer may be in contact with the treatment centre over long periods and could be particularly affected. This study aimed to identify haematological cancer patients’ perceptions of supportive design elements in the hospital they attended and associations with self-reported mood or well-being. Outpatients from three large metropolitan hospitals in Australia were mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The comfort and compliance of patients with cancer may be impacted by a crowded waiting space. 41 Well-trained advanced practice providers, such as nurse practitioners, physician assistants, and dedicated pharmacists, are essential to running the SDC clinic efficiently. It has been shown that granting advanced practice providers the ability to write prescriptions for chemotherapy and supportive care drugs can further improve cancer care and guarantee the highest level of safety while administering these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The comfort and compliance of patients with cancer may be impacted by a crowded waiting space. 41 Well-trained advanced practice providers, such as nurse practitioners, physician assistants, and dedicated pharmacists, are essential to running the SDC clinic efficiently. It has been shown that granting advanced practice providers the ability to write prescriptions for chemotherapy and supportive care drugs can further improve cancer care and guarantee the highest level of safety while administering these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…förvärra den upplevda stressen genom att främja en känsla av kontroll över den fysiska och sociala omgivningen, möjlighet till socialt stöd samt att ha tillgång till positiva distraktioner. Minskad stress främjar hälsa och välbefinnande (47) Fysiska faktorer såsom tillgång till dagsljus, möjligheten att se ut mot naturen, god ventilation och en enkel och begriplig design har visats ha positiva effekter på vården och hälsoprocesserna (37,52). Effekter i vårdmiljön kan uppnås genom att tillhandahålla fönster och belysning, att använda sig av färger, kontrollera temperatur och att ljudnivåer är lämpliga.…”
Section: Vårdmiljöunclassified